Identification of physical interaction between levodopa–benzerazide hydrochloride - Ilma Nugrahani; Sukmadjaja Asyarie; Sundani Noerono Soewandhi; Slamet Ibrahim (Indonesian Journal of Pharmacy, 2007)
The aim of this research was to investigate the possibility physical interaction occurred between of levodopa and benzerazide hydrochloride, which known as compounds used in combination for the the antiparkinson. The “cold contact methods” was used which was developed from Kofler contact method’s (hot stage methods). Thermograms Differential Scanning Calorimetry and difractograms X-Ray indicated that levodopa – benzerazide hydrochloride tent to form a peritecticum-molecular compound physical interaction with eutectics point at 4:6 and 9:1 molar ratios.Key words: benzerazide hydrochloride, cold contact method, levodopa, physical interaction.